Patients' genetic data protection in Polish law and EU law - selected issues - Michałowska, Kinga (Medicine, law & society, 2018)
The article entitled "Patients' genetic data protection in Polish law and EU law - selected issues" presents issues related to the protection of patients' rights and focuses on the legal basis for genetic testing and genetic data protection. Based on a comparison of regulations of international law and regulations on genetic tests introduced in foreign legal systems, the text analyzes the assumptions for the draft of the Polish act on genetic tests performed for health purposes. It presents the patient's consent to testing, the scope of information provided to the patient, the right to disclose research results to related persons and the protection of genetic data. In reference to the regulations set out in other acts, it was noted that they do not guarantee the protection of information obtained as a result of research. Due to the particular nature of genetic data, they require increased protection, which can be guaranteed through implementation of the Act on Genetic Research. In the final part, authors presented the most important achievements of the judicature of European Court of Human Rights in the field of genetic data protection.
Keywords: genetske raziskave; genetski podatki; pacientove pravice; zaščita genetskih podatkov; zdravstvena dokumentacija